Oral health of hospitalized elderly people: revelance of professional dentists in the treatment of diseases linked to oral health (Research, Society and Development, 2023)
The participation and work of the dental surgeon in the multidisciplinary team in hospitals are of paramount importance in subject's health treatment process, especially when it comes to the elderly patient, since this requires more care and attention. A narrative literature review was carried out in the databases between the years 2011 to 2023. The objective of this work is to analyze publications related to the relevance of the dental surgeon in the composition of the multidisciplinary team in alleviating the problems linked to issues of the oral cavity in the treatments of elderly health. And also address the importance of oral health with the maintenance of systemic health, highlighting the role of dentistry in intensive care units (ICU) and basically in elderly patients with pneumonia and/or other infections, highlighting the widespread importance of oral care for elderly patients, due to the predisposing factors resulting from aging, which may aggravate the proliferation of diseases in vulnerable elderly people in the oral cavity and given this multifactorial nature, the most debilitated people also have difficulties in sanitation.